FLORURO DE SODIO AL 5% POR IONTOFORESIS PARA EL TRATAMIENTO DE LA HIPERSENSIBILIDAD DENTINAL - Gomez J, Natalia; Moncada D, Cesar; Piedrahíta, Erika María; Velez J, Luis Fernando (CES Odontología, 2011)
El propósito de esta investigación fue el de disminuir al máximo y por un período de tiempo prolongado la hipersensibilidad dentinaria. Se utilizó floruro de sodio en solución al 5% y corriente eléctrica de 27 voltios y 0.7 miliamperios durante 3 minutos. Los resultados mostraron una eficacia del 83.19% al primer mes, 76.32% al tercer mes y 68.96% al sexto mes. Abstract The objective of this study was to evaluate the clinical effectiveness of iontophoresis with 5% sodium fluoride in reducing dentinal hypersensibility.- Patients were treated with 5% sodium fluoride using a 27v and 0.7 mA electric current during a three minute periodo Patients were evaluated one, three and six months later.- Results indicated an effectiveness of 83.19% one month later, 76.32% after three months and 68.95% after six months